GLUCOSE AND PROXIMATE ANALYSIS IN CEREALS SUBSTITUTING CASSAVA FLOUR AND RED BEANS - Tysa Runingsari; Dwi Kurnia Purnama Sari; Tri Yunita Fitria Damayanti (International Nutrition and Health Administrations Journal, 2024)
Diabetes mellitus is a disease or chronic metabolic disorder characterized by high blood sugar levels accompanied by disorders of carbohydrate, lipid and protein metabolism as a result of insulin function insufficiency. Diabetics are advised to pay attention to the food they consume, preferably low in sugar. In general, cereals on the market are made from wheat flour which contains quite a lot of sugar, so it is necessary to modify cereal recipes to increase nutritional value. Cassava flour is a food source of carbohydrates with a lower calorie content than wheat flour. Red bean flour has a fairly high protein content and a low glycemic index, so the substitution of cassava flour and red bean flour is expected to increase the nutritional value. This study aims to determine the effect of substituting cassava flour and red bean flour on the nutritional value of cereals. This research used True Experimental with 4 treatment levels and 6 replications. The treatment applied was the ratio of wheat flour: cassava flour: red bean flour at each P0 (100:0:0), P1 (10:50:40), P2 (10:60:30), P3 (10: 70:20). Based on the research results, it shows that there is an effect of reducing glucose, energy, fat, carbohydrate and water levels compared to those without substitution. There was an increase in protein and ash content in the treatment. The cereal formulation that has the expected nutritional content is the P3 formulation